Weightlifting exercises as means of developing physical training of military personnel - Fedak S.S; Sevidova G.O (Kharkov National Pedagogical University, 2010)
The method of physical preparation of military personnel of higher soldiery educational establishments is improved. In an inspection took part 32 servicemen. Military personnel executed tests: at run on 100 and 3000 meters, undercutting on a cross-beam. Influence of employments is certain power exercises on speeding up, force and endurance of military personnel of speciality physical education. The level of influence of employments power exercises is set on physical possibilities of military personnel.